2018
DOI: 10.3390/s18020370
|View full text |Cite
|
Sign up to set email alerts
|

Securing Cooperative Spectrum Sensing Against Collusive SSDF Attack using XOR Distance Analysis in Cognitive Radio Networks

Abstract: Cooperative spectrum sensing (CSS) is considered as a powerful approach to improve the utilization of scarce spectrum resources. However, if CSS assumes that all secondary users (SU) are honest, it may offer opportunities for attackers to conduct a spectrum sensing data falsification (SSDF) attack. To suppress such a threat, recent efforts have been made to develop trust mechanisms. Currently, some attackers can collude with each other to form a collusive clique, and thus not only increase the power of SSDF at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Zhang et al 12 analyzed a generalized probabilistic soft SSDF attack model and deduced a closed-form expressions of global sensing performance at the FC. In the study by Singh et al, 13 a distance-based outlier detection approach is proposed to isolate the malicious nodes from the decision process. In the study by Ahmadfard et al, 14 a flexible structure is introduced to deal with the uncertain attacking parameters settings by attackers, and a soft-decision-based defense strategy is employed at FC to detect the attackers.…”
Section: Related Workmentioning
confidence: 99%
“…Zhang et al 12 analyzed a generalized probabilistic soft SSDF attack model and deduced a closed-form expressions of global sensing performance at the FC. In the study by Singh et al, 13 a distance-based outlier detection approach is proposed to isolate the malicious nodes from the decision process. In the study by Ahmadfard et al, 14 a flexible structure is introduced to deal with the uncertain attacking parameters settings by attackers, and a soft-decision-based defense strategy is employed at FC to detect the attackers.…”
Section: Related Workmentioning
confidence: 99%
“…In [23], Jaglan et al introduced artificial neural network (ANN) at the FC thereby achieving significant improvement in detection performance and reduction in false alarm rate as compared to conventional schemes. Feng et al reported the collusive SSDF attack method and proposed a two-level (the request-level and feedback-level) and XDA defence scheme from the perspective of XOR distance analysis to defend against this attack in [24,25], respectively. Khan et al in [26] proposed a double adaptive thresholding technique in order to differentiate legitimate users from doubtful and malicious users.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al [1] have advocated certificate-based trust worth respect for the behaviour of SUs in a distributed manner. Feng et al [5] have presented an XOR distance analysis to suppress the collusive SSDF attack. Zhao et al have addressed a dynamic collusive SSDF attack based on a trust fluctuation clustering analysis to measure the similarities between two attackers that reflect the trust values [6].…”
Section: Related Workmentioning
confidence: 99%